Entrepreneur magazine’s ultimate book of sales letters : - Kimball, Cheryl (Entrepreneur Press, 2007)
The book privides an oveview of the basic types of written sales communication situations, including sales letter strategies, style, format, and e-mail and fax; also including model letters